The equation is true for a constant .
What is the value of
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Begin with the substitution u = x t , yielding :
x → 0 lim ∫ 0 1 ( x − sin x ) a + x u x 3 u 2 d u = 1
The x u in the square-root is neglected , as it tends to zero. Now work on the limit of x alone:
x → 0 lim x − sin x x 3
It is quite easy; Apply L'Hospital three times to get the value of 6 . So our initial equation became:
∫ 0 1 a 6 u 2 d u = 1
Now nothing but easy integration and solving an equation gives a = 4 .